Lived experiences of Palestinian patients with COVID-19: a multi-center descriptive phenomenological study of recovery journey - Aidah Alkaissi; Fadi Zaben; Mohammad Abu-Rajab; Mahdia Alkony (BMC, 2022)
Abstract Background Exploring lived experiences of recovered COVID-19 patients might have scientific, social, and policy relevance that can apply to the healthcare infrastructure. This multi-center descriptive phenomenological study was conducted to explore lived experiences of Palestinian patients who recovered from COVID-19.  Methods This was a descriptive phenomenological study. A purposive sampling technique was used to recruit the study participants. Semi-structured qualitative interviews were conducted with patients who recovered from COVID-19 (n = 20). The interviews were transcribed verbatim. The transcripts were analyzed using Colaizzi's phenomenological approach which consisted of the following steps: 1) familiarization, 2) identification of significant statements, 3) formulation of the meanings, 4) clustering the themes, 5) development of an exhaustive description of the phenomenon, 6) production of the fundamental structure, and 7) verification of the fundamental structure. Results Semi-structured interviews were conducted with 14 male and 6 female patients who recovered from COVID-19. The total duration of the interview time was 998 min (16.6 h). The qualitative data collected during the interviews were categorized into 5 major themes and 16 subthemes that exhaustively described the phenomenon. The major themes were relevant to: 1) emotions after learning about the infection, 2) experiencing social exclusion and stigma, 3) the experienced symptoms, 4) supportive treatments, herbs, rituals, and social support, 5) and life after recovery. Conclusion The interviewees recounted experiencing negative emotions, social exclusion, and stigma because of their infection. It may be important for mental health promotion to be an integral part of the care plan for patients with COVID-19. More studies are still needed to investigate if introducing mental healthcare providers to the care team of patients with COVID-19 can improve the experiences of the patients.